Analisis dan Korelasi Genetik Pertambahan Sifat Agronomi Dengan Sifat Fisiologi Kopi Arabika Sumatera Budidaya Kawasan Pesisir - Alnopri, Alnopri; Siswanto, Usman; Nurjannah, Uswatun; Panjaitan, Amisah Patel (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Alnopri, A., Nurjanah, S. U., Panjaitan, A. P. (2024). Genetic analysis and correlation of agronomic traits with physiological traits of sumatra arabica coffee cultivated in coastal Areas. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp.591–599). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The coastal area is a transitional, namely the land is still influenced by marine activities, such as tides, sea breezes and saltwater seepage. Arabica coffee on Sumatra Island is cultivated in the highlands, namely in the Bukit Barisan Area. The Acc Research Land (Alnopri Coffee Centre) is located in a coastal area with an altitude of 10 meters above sea level. Acc land have a experimental garden arranged with a Randomized Block Design, by planting 9 genotype of Arabica Coffee from Sumatra Island and repeated 3 times. The long-term goal is to obtain information on adaptive genotype of cultivation in coastal areas. This experiment was conducted to determine growth patterns, analysis and genetic correlation of increase in agronomic and physiological traits. The study was carried out in the immature plant phase for two years, namely the 2023 dry season and the 2024 rainy season. The analysis carried out was by analysis of variance and analysis of covariance. The results of the study showed that the growth pattern was normal and had increased from the previous year, the increase in the number of leaves and chlorophyll content differed between genotypes, and the genetic correlation between the increase in agronomic traits and physiological traits with a very weak to strong relationship. The conclusion of this study is 1). The growth pattern of agronomic traits (plant height and canopy area) of cultivated Arabica coffee in coastal areas is normal, 2). The increase in traits the number of internodes, the area of a pair of leaves, and chlorophyll content shows that the Mandailing and Sigararutang genotype are the best, and 3). The genetic correlation of the increase in agronomic traits and physiological traits that are strong correlation are the variables of canopy area and leaf pair area.